Effect of Fiber Content and Water Absorption Behaviour on the Mechanical Properties of Screw Pine Fiber-reinforced Vinyl Ester Composites - Venkatarajan SUBBARAYALU; Subbu CHINNARAMAN; Athijayamani AYYANAR; Rajamuneeswaran SUBBAIYARAJA (Medžiagotyra)
This study examines how water exposure affects the mechanical properties of randomly oriented screw pine fiber reinforced vinyl ester composites. Composite specimens have been produced using the compression moulding process with three different fibre content values (12.75, 26.19, and 40.39 vol.%). For 5 days, the produced composite specimens were immersed in three different water environments: seawater, groundwater, and distilled water, to investigate the effect of water absorption on the mechanical properties of composites. The mechanical properties of composites under wet conditions were compared to those in dry conditions, and they were found to decrease when water particles were absorbed. In both dry and wet conditions, the composite with a volume of 26.19 % has the highest tensile, flexural, and impact strength values. Mechanical properties were drastically lowered in wet conditions compared to dry conditions. It was revealed that exposure to seawater has a significant effect on composite properties when compared to ground and distilled water exposure. The fractured surface of composite specimens was examined under a scanning electron microscope following exposure to three different water conditions. Scanning electron microscopy revealed resin losses, void formation, and microcracks on the surface of the wet composite specimens.